Wedding E-Registration At The Android Based On KUA, Kedondong District - Tri Susilowati; Widianto Widianto; Nuzul Ramadhani (Journal of Intelligent Business and Technology Science (JIBTec), 2021)
The Office of Religious Affairs (KUA) is an institution under the auspices of the Ministry of Religion of the Republic of Indonesia and carries out tasks based on government regulations, both the marriage law and the regulation of the Minister of Religion. This institution is also one of the marriage registration institutions in charge of registering and taking care of the completeness of marriage administration. Based on the data that has been surveyed at the KUA of Kedondong District, there are almost 50 pairs of prospective married couples who registered for marriage. KUA Kedondong District admitted that he was still burdened with the manualization process in recording data on prospective married and married couples face-to-face registration with KUA officers so that it is less effective and efficient in time management.Registration via the internet or Android is a good approach to increasing accessibility for the community. The research method used is quantitative and qualitative.While the system development method used is the SDLC (software development life cycle) method, namely the waterfall method, so that it can produce an application that can assist in the performance of KUA, namely the Online Marriage Registration Application at KUA Kedondong District.